Front Cover: Origin of the Aggregation‐Induced Phosphorescence of Platinum(II) Complexes: The Role of Metal–Metal Interactions on Emission Decay in the Crystalline State (Chem. Asian J. 20/2021). Issue 20 (27th September 2021) - Inoue, Ryo; Naota, Takeshi; Ehara, Masahiro
Abstract : The Front Cover, "Shachihoko " (Protectors of Nagoya Castle in Japan), represents two potential energy surfaces of the excited triplet state of Pt(II) complexes in the crystalline state with and without metal‐metal interaction, which are crucial for the expression of phosphorescent aggregation‐induced emission (AIE). This work describes, for the first time, phosphorescent deactivation processes of four class of AIE‐active Pt(II) complexes in the crystalline state based on experimental and theoretical investigations. Furthermore, the role of metal‐metal interaction in AIE has been clarified by comparing two computational models. More information can be found in the Full Paper by Ryo Inoue, Takeshi Naota, and Masahiro Ehara.